Sosialisasi Pemanfaatan dan Pemetaan Ruang Terbuka Hijau di Kota Pagar Alam - Dhiniati, Fameira; Azizah, Barrorotul; Edowinsyah, Edowinsyah (Universitas Pahlawan Tuanku Tambusai, 2025)
Green open space has ecological, social and aesthetic functions. Green open space is very important in improving the quality of a healthy, aesthetic and sustainable environment, especially in urban areas which are experiencing rapid growth. Pagar Alam City has physically met the need for green open space, because most of the land use is protected forest. However, Pagar Alam City still has to maintain the existence of urban green open spaces. The sosialization and mapping activities aim to increase public awareness and understanding of the importance of green open spaces, both from an environmental, social and economic perspective, as well as identifying the existence of green open spaces in Pagar Alam City. Socialization is carried out through direct counseling, interactive discussions, and the distribution of educational media to the community in the Pagar Alam City area. Participatory methods are applied so that the community is involved in planning, utilizing and preserving green open space. The results of the activity show an increase in public knowledge about the benefits of green open space and community initiatives to support nature conservation have emerged. Mapping activities provide skills to the community in identifying green open spaces.